Transition Trauma Metaphor in Transgender Narrative - Martynyuk , Alla (East European Journal of Psycholinguistics, 2021)
This study combines methodological tools of conceptual metaphor theory and narrative psychology with theoretical assumptions of the intersubjective psycholinguistic approach to meaning to explore instantiations of transition narrative metaphors in 16 TED talks given by transgender people and posted on the TED platform within the period between January 2013 and July 2020. The speakers are aged from 20 to 70; 8 males and 8 females; 2 black and 9 white Americans, 2 Filipinos, 1 black South-African, 1 Puerto Rican, and 1 white Australian. The study offers a new interpretation of narrative metaphor based on the intersubjective model of meaning. Within this model, narrative metaphor is conceived as extended conceptual metaphor instantiated in a number of multimodal metaphoric expressions made coherent by the textual, social, cultural, and historical context of the narrative, but primarily by its interactive situational context, which includes the audience into the narrative through empathy and gives them power to change the narrative. The research reveals that all the 16 analysed narratives rest on the TRANSITION IS CONTEST narrative metaphor that represents a conflict between positive self-evaluation of transition by a transgender individual and its negative evaluation / unacceptance by the society, which makes transition a traumatic experience. The density of words and phrases instantiating the CONTEST metaphor in the 16 narratives varies from 2,5 to 3 % which means that they are key linguistic expressions of the narratives. The CONTEST metaphor provides a deeper insight into transgender transition compared to the JOURNEY/TRAVEL metaphor found to represent transition experience in existing cognitive linguistic and transgender studies. The JOURNEY/TRAVEL metaphor fails to grasp the intersubjective and, consequently, traumatic nature of transition experience. The results of the research suggest that narrative as well as narrative metaphor can be given a more accurate interpretation if they are approached from the intersubjective perspective, which reflects their true nature as socially and culturally shaped interactive phenomena.